Parental Narratives of Bonding and Relational Experiences with Preterm Infants Born at 23 to 24 Weeks-A Qualitative Descriptive Study - Anniina Väliaho; Liisa Lehtonen; Anna Axelin; Riikka Korja (MDPI AG, 2023)
(1) Background. The birth of an infant at 23 to 24 weeks poses a significant challenge to healthy parent-infant bonding because of the high risk of infant loss and the prolonged separation. The aim of this study was to retrospectively explore the narratives of parents with children born at 23-24 weeks about their bonding formation and relational experiences. (2) Methods. This was a qualitative descriptive study conducted with Finnish parents of children born at 23 or 24 weeks of gestation. Twenty-nine mothers and eight fathers were retrospectively interviewed using a semi-structured interview about the bonding process with their infant during the period in the neonatal intensive care unit (NICU) and their later parent-child relationship. Parents' narratives were deductively analysed according to a framework previously developed for studying parental bonding. (3) Results. Our results showed that several parents described the bonding process as natural or even easy despite the traumatic start to parenthood. Support from NICU staff and providing opportunities for participation in infant care and parent-infant physical closeness were reported to enhance the bonding process. Our study identified earlier parenting experience as a new element supporting bonding. (4) Conclusions. According to our results, essential elements enhancing parent-infant bonding in NICU settings seem to be supporting parents psychologically, promoting parent-infant closeness, and encouraging parental participation in the infants' care, even with the most immature infants.